Wetland expansion on the continental shelf of the northern South China Sea during deglacial sea level rise. (1st March 2020) - Chen, Yunru; Huang, Enqing; Schefuß, Enno; Mohtadi, Mahyar; Steinke, Stephan; Liu, Jingjing; Martínez-Méndez, Gema; Tian, Jun
Abstract: To identify environmental causes for past changes in vegetation in subtropical East Asia, we present carbon isotope compositions of plant-wax n -alkanes and provide estimates of the C4 -plant contribution across the past four glacial terminations and interglacials, based on cores recovered from the northern South China Sea. Our results show a comparable C4 -plant contribution between the Last Glacial Maximum (LGM) and the Holocene. An increase of the C4 -plant contribution by 15–20% is found for Terminations IV, II and I relative to subsequent interglacial peaks, coeval with an expansion of Cyperaceae and Poaceae. In contrast, Termination V reveals a lower C4 -plant contribution than Marine Isotope Stage (MIS) 11c. The data exhibit a long-term trend, with a stepwise increase of the C4 -plant contribution across interglacials MIS 11c, 9e, 7e and 1. We suggest that no substantial changes in humidity levels over glacial-interglacial cycles occurred facilitating a similar C3 /C4 -plant ratio for the LGM and the Holocene. Instead, deglacial sea-level rises caused an extensive development of floodplains and wetlands on the exposed continental shelf, providing habitats for the spread of C4 sedges and grasses. The progressive subsidence of Chinese coastal areas and the broadening of the continental shelf over the late Quaternary explains the nearly absence of C4 plant occurrence during Termination V and a gradual increase of the C4 -plant contribution across interglacial peaks. Taken together, changes in coastal environments should be considered when interpreting marine-based vegetation reconstructions from subtropical Asia. Highlights: High-resolution plant-wax δ 13 C records for past four interglacials and glacial terminations. C4 -plant expansions on the exposed continent shelf occurred over glacial terminations. Changes in coastal environments rather than climate cause alterations of vegetation composition. Progressive broadening of the continental shelfs explains long-term vegetation changes.